Biodegradation of MC-LR and its key bioactive moiety Adda by Sphingopyxis sp. YF1: Comprehensive elucidation of the mechanisms and pathways. (1st February 2023) - Wei, Jia; Pengji, Zhou; Zhang, Jiajia; Peng, Tangjian; Luo, Jiayou; Yang, Fei
Highlights: Biodegradation mechanisms of MC-LR and its key bioactive moiety Adda were elucidated. Multi-omic profiles of Sphingopyxis sp. YF1 in Adda degradation were firstly revealed. The aminotransferase and beta oxidation enzymes played important roles in Adda biodegradation. Some novel MC-LR and Adda biodegradation products were identified successfully. Abstract: Microcystins (MCs) are harmful to the ecology and public health. Some bacteria can degrade MCs into Adda, but few can destroy Adda. Adda is the key bioactive moiety of MCs and mainly contributes to hepatotoxicity. We had previously isolated an indigenous novel bacterial strain named Sphingopyxis sp. YF1 that can efficiently degrade MCs and its key bioactive moiety Adda, but the mechanisms remained unknown. Here, the biodegradation mechanisms and pathways of Adda were systematically investigated using multi-omics analysis, mass spectrometry and heterologous expression. The transcriptomic and metabolomic profiles of strain YF1 during Adda degradation were revealed for the first time. Multi-omics analyses suggested that the fatty acid degradation pathway was enriched. Specifically, the expression of genes encoding aminotransferase, beta oxidation (β-oxidation) enzymes and phenylacetic acid (PAA) degradation enzymes were significantly up-regulated during Adda degradation. These enzymes were further proven to play important roles in the biodegradation of Adda. Simultaneously, some novel potential degradation products of Adda were identified successfully, including 7‑methoxy-4, 6-dimethyl-8-phenyloca-2, 4-dienoic acid (C17 H22 O3 ), 2-methyl-3‑methoxy-4-phenylbutyric acid (C12 H16 O3 ) and phenylacetic acid (PAA, C8 H8 O2 ). In summary, the Adda was converted into PAA through aminotransferase and β-oxidation enzymes, then the PAA was further degraded by PAA degradation enzymes, and finally to CO2 via the tricarboxylic acid cycle. This study comprehensively elucidated the novel MC-LR biodegradation mechanisms, especially the new enzymatic pathway of Adda degradation. These findings provide a new perspective on the applications of microbes in the MCs polluted environment. Graphical abstract: Image, graphical abstract